The black revolution in Medina in the year 145 AH / 762 AD (Journal of the College of Basic Education, 2023)
No human race has endured as the black race endured the suffering of life, as it was sold, captured, captured, killed and mutilated, and it did not deal with it humanely throughout human history. And although this race enjoyed high roughness, patience, gladiation, enduring hardships, and obedience to its masters who exploited it in the worst exploitation, yet throughout history it was able to record for itself in the history record revolutionary epics and liberation uprisings that the history of humanity witnessed to it and throughout the ages, as we do not find a civilization except And we find the black race a role in its industry, and we find in addition to that a liberation revolution or an attempt to get out of the domination of slavery, and although most of them did not achieve their goals, they were able, over the ages, to crystallize a human concern that stands by them and pushes towards their justice.